Imperialism and Subimperialism in Mainland Southeast Asia: Quantifying Relations of Unequal Exchange - Thame, Charlie; Rue-Glutting, Jana-Chin (รัฐศาสตร์นิเทศ, 2025)
This article presents results of an exploratory study on imperialism and subimperialism in the Mekong subregion, including an overview of classical and contemporary debates on imperialism and methodologies developed to quantify unequal exchange. It extends these to analyse trade and investment trends based on existing data for the subregion. Previous studies have incorporated analysis of Thailand and Vietnam, this is the first to incorporate Myanmar, Laos, and Cambodia too. It finds existing data is inadequate but also evidence that Thailand and to a lesser extent Vietnam have benefited from subimperialist relations with neighbouring countries at the expense of ecology and fractions of labour. It concludes that developing countries should remain sceptical of mainstream development economics and statistical data based on them and that Thailand and Vietnam can be considered subimperialist powers with a functional role of mediating imperialist relations between the subregion and the world market. The research contributes to historical materialist scholarship on the international relations and development of mainland Southeast Asia and the political economy of contemporary imperialism and has implications for subaltern classes across the subregion and other peripheral and semi-peripheral economies across the world. It can also be used to support future research that challenges realist, liberal, and constructivist approaches to minilateral institutions such as the GMS, ACMECS, and the LMC from a historical materialist perspective.